Solve all your doubts with Teachoo Black (new monthly pack available now!)

Are you in **school**? Do you **love Teachoo?**

We would love to talk to you! Please fill this form so that we can contact you

Examples

Example 1

Example 2

Example 3

Example 4

Example 5 Important

Example 6 Deleted for CBSE Board 2023 Exams

Example 7 Deleted for CBSE Board 2023 Exams

Example 8 Deleted for CBSE Board 2023 Exams

Example 9 Important Deleted for CBSE Board 2023 Exams

Example 10 Important Deleted for CBSE Board 2023 Exams

Example 11 Deleted for CBSE Board 2023 Exams

Example 12 Deleted for CBSE Board 2023 Exams

Example 13 Deleted for CBSE Board 2023 Exams

Example 14 Important Deleted for CBSE Board 2023 Exams

Example 15 Important Deleted for CBSE Board 2023 Exams

Example 16 Important Deleted for CBSE Board 2023 Exams

Example 17

Example 18 Important

Example 19

Example 20

Example 21

Example 22 Important

Example 23

Example 24 Important

Example 25

Example 26 Important

Example 27

Example 28 Important

Example 29

Example 30

Example 31 Important Deleted for CBSE Board 2023 Exams

Example 32 Important Deleted for CBSE Board 2023 Exams

Example 33 Important You are here

Example 34 Important Deleted for CBSE Board 2023 Exams

Chapter 4 Class 12 Determinants

Serial order wise

Last updated at Jan. 23, 2020 by Teachoo

Example 33 Use product [■8(1&−1&2@0&2&−3@3&−2&4)] [■8(−2&0&1@9&2&−3@6&1&−2)] to solve the system of equations x – y + 2z = 1 2y – 3z = 1 3x – 2y + 4z = 2 Consider the product [■8(1&−1&2@0&2&−3@3&−2&4)] [■8(−2&0&1@9&2&−3@6&1&−2)] =[■8(1(⤶7−2)+(⤶7−1)(9)+2(6)&1(0)+(−1)(2)+2(1)&1(1)+(−1)(−3)+2(−2)@0(−2)+2(9)+(−3)(6)&0(0)+2(2)+(−3)(1)&0(1)+0(−3)+(−3)(−2)@3(−2)+(−2)(9)+(6)&3(0)+(−2)(2)+4(1)&3(1)+(−2)(−3)+4(−2))] = [■8(−2−9+12&0−2+2&1+3−4@0+18−18&0+4−3&0−6+6@−6−18+24&0−4+4&3+6−8)] = [■8(1@0@0)" " ■8(0@1@0)" " ■8(0@0@1)] We know that AA-1 = I So [■8(−2&0&1@0&2&−3@6&1&−2)] is inverse of [■8(1&−1&2@0&2&−3@3&−2&4)] i.e. [■8(𝟏&−𝟏&𝟐@𝟎&𝟐&−𝟑@𝟑&−𝟐&𝟒)]^(−𝟏)= [■8(−𝟐&𝟎&𝟏@𝟗&𝟐&−𝟑@𝟔&𝟏&−𝟐)] Given equations are x – y + 2z = 1 2y – 3z = 1 3x – 2y + 4z = 2 Writing the equation as AX = B [■8(1&−1&2@0&2&−3@3&−2&4)] [■8(𝑥@𝑦@𝑧)] = [■8(1@1@2)] Here A [■8(1&−1&2@0&2&−3@3&−2&4)], X = [■8(𝑥@𝑦@𝑧)] & B = [■8(1@1@2)] Now, AX = B X = A-1 B Here A = [■8(1&−1&2@0&2&−3@3&−2&4)] So, A-1 = [■8(1&−1&2@0&2&−3@3&−2&4)]^(−1)= [■8(−2&0&1@9&2&−3@6&1&−2)] Now, X = A-1 B Putting Value [■8(𝑥@𝑦@𝑧)] = [■8(−2&0&1@9&2&−3@6&1&−2)] [■8(1@1@2)] = [■8(−2&0&1@9&2&−3@6&1&−2)] [■8(1@1@2)] (Calculated above) [■8(𝑥@𝑦@𝑧)] = [■8(−2(1)+0(1)+1(2)@9(1)+2(1)−3(2)@6(1)+1(1)−2(2))] [■8(𝑥@𝑦@𝑧)] =[■8(−2+0+2@9+2−6@6+1−4)] [■8(𝑥@𝑦@𝑧)] = [■8(0@5@3)] Hence, x = 0 , y = 5 & z = 3